Analysis of Tall Building with Different Lateral Force Resisting System (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the current circumstance, the populace is  expanding rapidly, thus, the urban areas are becoming wide  by devouring farming and green space and the land esteem  is expanding. Another point is the tall vertical structure  speaks to the country. As it builds the notoriety of the  nation. To keep away from this the structures began  developing vertical and thin as it arrives at a specific height  the wind force governs the building as the main load more  than gravity load, as the building grows higher the stability  reduces. Due to a lack of design to face wind loads, as the  cross-section decreases the stability reduces. And these  structures are more prone to earthquakes and wind.  Therefore, much research is proceeding to balance out the  structure from an increasingly affordable perspective. To  know the best performance and economical for the lateral  force-resisting system of different types of 30 story  buildings are modelled in ETABS, assuming the site  location as BHUJ Gujarat, India. For the different structural  systems that are compared for minimum story displacement  and minimum story drift, these are the qualities that  characterize the human comforts for the structure. the  structural system used is conventional, shear wall, truss  belt, outrigger, diagrid, and fluid viscous damper are used  to compare the best performance of the structure. Above all  diagrid and viscous damper shows the less displacement  and drift values when compared to others but from the  economic point of view viscous damper gives the best result  from all the above.
Keywords: Conventional; Shear-wall; Truss-belt; Outrigger; Diagrid; Viscous damper; Response spectrum, ETABS